Diurnal variations of cold-induced thermogenesis in young, healthy adults: A randomized crossover trial - Acosta Francisco M; Sanchez-Delgado Guillermo; Martinez-Tellez Bonja; Alcantara JMA; Llamas-Elvira Jose M; Ruiz Jonatan R (Netherlands, 2022)
Background: Harnessing cold-induced thermogenesis (CIT) and brown adipose tissue (BAT) activity has been proposed as a means of counteracting a positive energy balance, and thus of combating obesity and its related comorbidities. However, it has remained unclear whether CIT and BAT activity show diurnal variation in humans - knowledge that might allow treatments based on these factors to be time-optimized.
Methods: A randomized crossover experiment was designed to examine whether CIT shows morning/evening variation in young, healthy adults (n = 14, 5 women). On the first experimental day, subjects' shivering thresholds were determined following a cooling protocol. After ≈96 h had elapsed, the subjects then returned on two further days (approx. 48 h apart) at 08:00 h or 18:00 in random order. On both the latter days, the resting energy expenditure (REE) was measured before the subjects underwent personalized cold exposure (i.e., according to their shivering threshold). CIT was then assessed for 60 min by indirect calorimetry. In an independent cross-sectional study (n = 133, 88 women), subjects came to the laboratory between 8:00 and 18:00 h and their BAT 18F-fluordeoxyglucose (18F-FDG) uptake was assessed after personalized cold stimulation.
Results: Both the REE and CIT were similar in the morning and evening (all P > 0.05). Indeed, 60 min of personalized-mild cold exposure in the morning or evening elicited a similar change in energy expenditure (16.8 ± 12.8 vs. 15.7 ± 15.1% increase above REE, P = 0.72). BAT 18F-FDG uptake was also similar in the morning, evening and afternoon (all P > 0.05).
Conclusion: CIT does not appear to show morning/evening variation in young healthy adults, with the current study design and methodology. BAT 18F-FDG uptake appears not to change across the day either, although experiments with a within-subject study design are needed to confirm these findings. Registered under ClinicalTrials.gov Identifier no. NCT02365129.